2013
DOI: 10.1016/j.ajodo.2012.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum neurotoxin type A in the masseter muscle: Effects on incisor eruption in rabbits

Abstract: Introduction Botulinum neurotoxins are responsible for the paralytic food poisoning, botulism. Commercial formulations such as botulinum neurotoxin type A are increasingly used for various conditions, including cosmetic recontouring of the lower face by injection of the large masseter muscles. The paralysis of a major muscle of mastication lowers occlusal force and thus might affect tooth eruption. The purpose of this study was to investigate the effects of unilateral masseter muscle injection of botulinum neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In fact, Btx has been used for more than a decade to cause limb paresis in rodents and rabbits as a model of disuse osteopenia 10,11 . For example, one study using a rabbit model found that a single unilateral masseter muscle Btx injection produced “profound” morphological changes and bone loss in the mandibular condyle, as well as bone loss in the alveolar region 12,13 similar to that found in other more recent rodent and rabbit studies 14‐16 . In addition to the impact of muscle paresis on bone, Btx may also have direct effect on bone resorption.…”
Section: Introductionmentioning
confidence: 67%
“…In fact, Btx has been used for more than a decade to cause limb paresis in rodents and rabbits as a model of disuse osteopenia 10,11 . For example, one study using a rabbit model found that a single unilateral masseter muscle Btx injection produced “profound” morphological changes and bone loss in the mandibular condyle, as well as bone loss in the alveolar region 12,13 similar to that found in other more recent rodent and rabbit studies 14‐16 . In addition to the impact of muscle paresis on bone, Btx may also have direct effect on bone resorption.…”
Section: Introductionmentioning
confidence: 67%
“…15 The uninjected-side condyle was within normal limits for all parameters at all times, as was the saline-injected-side condyle. Loading of the injected-side condyle was reduced rather than removed, and the rabbits chewed normally, 26 presumably because the other jaw closing muscles (uninjected masseter plus medial pterygoids and temporales) remained active. The microCT measurements verified overall bone loss was restricted to the BoNT/A-side condyle, but BoNT/A group animals showed extreme variability at the 12-week timepoint, with some injected-side condyles showing minimal recovery and others showing more bone than the opposite, uninjected-side condyle.…”
Section: Discussionmentioning
confidence: 99%
“…Masticatory muscle hypofunction caused by BTX injection decreases the bite force and affects the dental occlusion and tooth eruption [ 19 , 20 ]. The masseter muscle volume and weight are significantly reduced by BTX injection [ 19 ], and the maximum bite force is also decreased [ 57 ].…”
Section: Broken Balance Muscle Function By Btx Injection and Its Ementioning
confidence: 99%
“…Furthermore, the maxilla and mandibular molar height are also increased after BTX injection into the masseter muscle [ 17 ]. Masticatory muscle weakness caused by BTX injection affects the tooth eruption state [ 19 , 20 ], and this tooth overeruption can affect the facial morphological changes, such as anterior open-bite, increased anterior facial height, and dolichofacial morphology [ 58 , 59 ].…”
Section: Broken Balance Muscle Function By Btx Injection and Its Ementioning
confidence: 99%
See 1 more Smart Citation